Predictive value of extreme low PAPP-A, free βhCG and extreme high mean uterine artery pulsatility index in the first trimester for fetal growth restriction - Lukić, Relja; Karadžov-Orlić, Nataša; Egić, Amira; Damnjanović-Pažin, Barbara; Miković, Željko (Vojnosanitetski pregled, 2021)
Background/Aim. Adverse pregnancy outcomes such as preeclampsia (PE), placental abruption (PA), fetal intrauterine growth restriction (IUGR) and stillbirth could be recognized by prenatal screening. The objective of this study was to predict IUGR by using first-trimester extremely low pregnancy-associated plasma protein-A (PAPP-A), extremely low free beta-human chorionic gonadotropin (free βhCG) levels, and extremely high Pulsatility-index (PI) of uterine arteries, as single and combined predictors for IUGR development. Methods. This was a prospective first-trimester study analyzing singleton pregnancies at 11–13+6 weeks’ gestation who underwent routine first-trimester screening at the Department of High Risk Pregnancy of the Clinic for Gynecology and Obstetrics „Narodni front“, University of Belgrade, Serbia. First-trimester screening for PAPP-A, free βhCG, and PI was performed in nulliparous, normotensive women with extremely low PAPP-A (PAPP-A ≤ 0.52 unit multiple of median – MoM) and/or extremely low free βhCG (free βhCG ≤ 0.56 MoM) and/or extremely high PI (PI ≥ 2.52). Results. Of 85 pregnant women included in the final analysis, 14 (16.5%) developed IUGR. PAPP-A ≤ 0.52 MoM and PI ≥ 2.52, as single categorical variables, found to be with high predictable values for IUGR development (odds ratio – OR = 3.064, 95% confidence interval – CI= 0.634-14.810, p = 0.046, and OR = 2.129, 95% CI = 0.449–10.713, p = 0.021, respectively). Furthermore, the receiver operating characteristic (ROC curve identified PAPP-A and PI as continuous variables to be significant predictors of IUGR (area under curve – AUC = 0.671, 95% CI = 0.521−0.820, p = 0.045, and AUC = 0.744, 95% CI = 0.587−0.902, p = 0.004, respectively). Conclusion. The present study suggests that the first trimester extremely low PAPP-A and increased Doppler-PI levels are single predictors of IUGR. Described model could be used in a routine daily clinical practice in resource limited settings where other parameters are not available for the prediction of IUGR development.